2021
DOI: 10.1002/smll.202103514
|View full text |Cite
|
Sign up to set email alerts
|

2D Hybrid Halide Perovskites: Structure, Properties, and Applications in Solar Cells

Abstract: Abstract2D metal‐halide perovskites have attracted intense research interest due to superior long‐term stability under ambient environments. Compared to their 3D analog, the alternate arrangement of organic and inorganic layers leads to forming a multilayer quantum well (MQW), which endows 2D perovskites with anisotropic optoelectronic properties. In addition, the spacer layer functions as a hydrophobic barrier to effectively prevent 2D perovskite films from ion migration and moisture penetrating, thus realizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 154 publications
(252 reference statements)
0
80
0
Order By: Relevance
“…S5, ESI †). Likewise, a visual inspection of GIWAXS images shows that (PDMA)PbI 4 crystallites have a preferred orientation, [9][10][11][12]27,34 whereas upon the gradual addition of F-PDMA continuous Debye-Scherrer rings appear, indicating a more random distribution of crystallites (Fig. 2d-f and Fig.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…S5, ESI †). Likewise, a visual inspection of GIWAXS images shows that (PDMA)PbI 4 crystallites have a preferred orientation, [9][10][11][12]27,34 whereas upon the gradual addition of F-PDMA continuous Debye-Scherrer rings appear, indicating a more random distribution of crystallites (Fig. 2d-f and Fig.…”
Section: Resultsmentioning
confidence: 88%
“…[6][7][8] In particular, two classes of 2D perovskite materials are of special interest, namely the Ruddlesden-Popper (RP) and Dion-Jacobson (DJ) phases. [9][10][11][12][13][14] RP systems mostly follow the general formula S′ 2 A n−1 M n X 3n+1 , where S′ are monofunctional spacers that interact with the perovskite slabs by forming a bilayer with a half-aunit-cell displacement between the perovskite slabs (Fig. 1b).…”
Section: Introductionmentioning
confidence: 99%
“…An alternately stacked layered structure will be constructed by insulating organic spacer layers (R‐NH 3 + ) and inorganic [PbI 6 ] 4− slabs. [ 79 ] The R‐NH 3 + organic amine layer should possess high hydrophobicity, suitable orientation, and dense accumulation to prevent direct contact between external water and perovskite. [ 80 ] However, the dielectric‐limited and quantum‐limited effects will lead an inferior carrier mobility/diffusion, which substantially hinders the photovoltaic performance of 2D PSCs.…”
Section: Improvement Of Fapbi3 Film Qualitymentioning
confidence: 99%
“…[ 80 ] However, the dielectric‐limited and quantum‐limited effects will lead an inferior carrier mobility/diffusion, which substantially hinders the photovoltaic performance of 2D PSCs. [ 79 ] Dimensional regulation can combine the superior charge transport property of 3D perovskite with the high stability of 2D perovskite, resulting in high‐efficiency and stable PSCs.…”
Section: Improvement Of Fapbi3 Film Qualitymentioning
confidence: 99%
“…This property can enhance the stability of intermediate phases and limited the release rate of PbI 2 , thus allowing spacer cations to have more time to participate in the crystallization reorganization and achieve vertical arrangements. 92 For instance, Jeon et al found that DMSO can form a stable MAI·PbI 2 ·DMSO intermediate phase via intercalating with the reactants within bulk solution. DMSO functions as a blender to delay the rapid reaction between PbI(Br) 2 and MAI(Br) during the thinning process, which makes the formation of uniformly high-quality films with large perovskite grains.…”
Section: Optimization Strategies For Crystallization Controlmentioning
confidence: 99%